Gut microbiome modulation by Weifuchun Capsules alleviates chronic atrophic gastritis: a combined microbiota and metabolomics approach - Xie, Weiwei; Wang, Nan; Wang, Ming; Zhang, Qian; Li, Wenyu; Zhang, Huiyi; Jin, Yiran; Du, Yingfeng (Frontiers in Microbiology, 2025)
BackgroundWeifuchun Capsule (WFC), a traditional Chinese medicinal formula containing Panax ginseng (red ginseng), Rabdosia rubescens, and Fructus Aurantii, is widely used clinically for the management of chronic atrophic gastritis (CAG). Although previous clinical evidence has demonstrated the efficacy of WFC in alleviating symptoms and improving gastric mucosal health, the precise mechanisms, particularly those mediated by gut microbiota, remain poorly understood. Given the crucial role of intestinal microbial dysbiosis in gastrointestinal disorders, exploring the microbiota-dependent pharmacological mechanisms of WFC is essential for understanding its therapeutic benefits in CAG.MethodsWe established a rat model of CAG to investigate the microbiota-associated mechanisms underlying the effects of WFC treatment. Integrated microbiome–metabolome analyses were performed, combining 16S rRNA gene sequencing for gut microbiota profiling and untargeted metabolomics to detect shifts in metabolic pathways. Network pharmacology identified bioactive compounds from 99 characterized components in WFC, with molecular docking analyses further validating these findings. Correlations between gut microbial composition and metabolic profiles were assessed using Spearman’s analysis, and western blotting was employed to evaluate inflammation-associated proteins.ResultsNetwork pharmacology screening identified 10 bioactive components from the 99 constituents present in WFC. Treatment with WFC significantly restored gut microbiota diversity and composition in CAG rats, notably enriching four bacterial families and ten genera. Metabolomic profiling revealed substantial regulation of glycerophospholipid and arachidonic acid metabolism, pathways intricately linked to microbial activity and gastrointestinal inflammation.ConclusionOur findings highlight that modulation of gut microbiota composition is central to the therapeutic effects of WFC on CAG. WFC exerts its gastroprotective activity primarily by reshaping specific gut microbial populations and subsequently normalizing associated metabolic pathways. This microbiome-oriented perspective provides new insights into traditional herbal medicine mechanisms, emphasizing the critical need to understand microbiota-mediated therapeutic strategies in gastrointestinal disorders.